Alcoholism in Families and Children Welfare in Kabale Municipality, Uganda. - Gumisirjza, Hillary (Kabale University, 2023)
The study examined the effect of alcoholism on families and children's welfare in Kabale Municipality, Uganda in Kabale municipality Kabale District. It was guided by four objectives which included; examining the causes of maternal alcoholism, examining the effect of maternal alcoholism on socio-economic status of the family, establishing the relationship between maternal alcoholism, socioeconomic status, and children's moral welfare, and establishing possible strategies for mitigating maternal alcohol abuse and enhance children's moral welfare. The study used a case study research design. The sample size that was used in this investigation was 59 respondents. The study adopted purposive sampling and snowball sampling as sampling techniques. The data collection methods included in-depth interviews, focus group discussion methods, and documentary reviews. The study revealed that the causes of alcoholism are high alcohol prevalence as reported, lack of a clear alcohol policy, cultural and traditional ceremonies, and poverty that causes redundancy. The study findings showed that alcoholism affects the socioeconomic status of the family through strained relationships as a result of physical confrontations. The study findings reported that alcohol usage negatively affects the welfare of Families through domestic violence, and loss of responsibility on families most of the people involved in alcohol have lost responsibility for families such as providing scholastic materials, and food. The study findings further showed the possible strategies for mitigating maternal alcohol abuse where it was reported that it can be mitigated by providing support through education. The study concludes that the alcohol prevalence in both local and manufactured alcoholic drinks accounts for high levels of alcohol use in the industrial division. Alcohol usage negatively affects the welfare of families in Kabale municipality through increased domestic violence and crime committed. There is a need for sensitization of the masses on the negative effects of alcohol usage on family welfare. The study recommends that there is a need for policies to place greater emphasis on parental alcohol misuse as distinct from other types of substance use. Policy documents focusing on family and child-related issues should refer to the impact of 'hidden harm' on children and young people's outcomes. Establishment of training programs for medical and social workers who can identify and provide the necessary counseling and advice to women who engage in hazardous, harmful or dependent alcohol consumption.